2002
DOI: 10.1542/peds.110.2.258
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled, Parallel-Group Study of SLI381 (Adderall XR) in Children With Attention-Deficit/Hyperactivity Disorder

Abstract: SLI381 produced consistent, dose-related improvements on all measures of efficacy. The extended-release nature of the SLI381 formulation was shown by continued, significant improvement in afternoon assessments by teachers and afternoon and late afternoon assessments by parents. The time course and therapeutic effects of SLI381 suggests that this medication is an efficacious once-daily treatment for children with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(94 citation statements)
references
References 17 publications
11
82
1
Order By: Relevance
“…Conventional medications are often very effective: effect sizes in studies of fure are in the range of a 50% reduction in symptoms after 1 week [27], whereas our study found a 25% reduction in symptoms after an average of 12.1 months.…”
Section: Discussioncontrasting
confidence: 62%
“…Conventional medications are often very effective: effect sizes in studies of fure are in the range of a 50% reduction in symptoms after 1 week [27], whereas our study found a 25% reduction in symptoms after an average of 12.1 months.…”
Section: Discussioncontrasting
confidence: 62%
“…These side effects appear to be similar during short-term treatment (Ϸ4 weeks) [101][102][103][104] and long-term maintenance. 100,105…”
Section: General Side Effects Of Stimulant Drugsmentioning
confidence: 77%
“…[103][104][105] Several studies report that nearly 90% of children will experience at least 1 side effect, but the majority are mild (63% to 69%) or moderate (28% to 34%), with 4% reporting severe side effects and with a 15% withdrawal rate from the study. 103,104 Decreased growth rate after long-term stimulant treatment also was highlighted in the naturalistic follow-up of children participating in the Multimodal ADHD study. 106 …”
Section: Safety Of Stimulant Drugs In Childrenmentioning
confidence: 99%
“…The CGI improvement subscale has been shown to be sensitive to medication effects in children 41 and in adults. 31 Based on previous studies in children, 26,32,42 the primary efficacy measure was defined as the change in the total investigator-rated ADHD RS score from baseline to the end of the 2-week double-blind period.…”
Section: Cgi Improvement Subscalementioning
confidence: 99%